Linguistic Landscape and Multicultural Dynamics in Pekanbaru: An Analysis of Culinary Business Names - Erdayani, Rizki; Budiarti, Dian; Firnadia, Evia (International Journal of English and Applied Linguistics (IJEAL), 2025)
Pekanbaru is one of Indonesia's urban areas inhabited by people from various ethnic and cultural backgrounds. This diversity is manifest in the linguistic landscape, particularly in the nomenclature of culinary enterprises. The objective of this study is to examine the use of language in culinary business names in the city of Pekanbaru using the Linguistic Landscape (LL) approach, from two fundamental functional perspectives: informational function and symbolic function. This study utilizes a qualitative research method characterized by a descriptive approach. The data was collected through a search of the "restaurant" category on the Google Maps platform, which yielded 232 data points on culinary brand names in Pekanbaru. The data was then subjected to a three-pronged analysis, with the aim of examining language usage patterns, the informational function, and the symbolic function. The analysis yielded two predominant patterns in language usage: monolingual and bilingual. In the context of informational function, culinary brand names tend to provide information about the type of food, characteristics of the dish, and price range. The findings of the study identified nine categories of culinary types from the displayed information. Conversely, from a symbolic standpoint, brand naming serves as a marker of affiliation with a distinct social identity. This study identified five forms of social identity represented through brand names, indicating the dynamics of social representation in the city's linguistic landscape.